Arts and the Public - Herring Paul D; Miller James E (The University Of Chicago Press, 1967)
Introduction, Skepticism and the Depth of Life, How Things Are, Culture and Humanity, Season of Counterfeit, On, The Unprincipled and Inconsequential Critic, Where the People Are, The Double Standard, Art Critisism Confidential, The Vanishing Spectator, Conversations on the Arts, The Visual Arts, Drama, Fiction, Art and Education.
Introduction, Skepticism and the Depth of Life, How Things Are, Culture and Humanity, Season of Counterfeit, On, The Unprincipled and Inconsequential Critic, Where the People Are, The Double Standard, Art Critisism Confidential, The Vanishing Spectator, Conversations on the Arts, The Visual Arts, Drama, Fiction, Art and Education.